Cranial MRI in neurosarcoidosis: Imaging patterns and nationwide clinical correlations - Uzun Ata, Elif; Guven, Serdar Can; Kucuksahin, Orhan; Ulgu, Mustafa Mahir; Birinci, Suayip (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Object: To investigate cranial MRIs of sarcoidosis pateints by defining typical and atypical findings and their relations with patient characteristics and other disease manifestations.Materials and Methods: A nationwide cohort was formed from patients with an entering ICD-10 code for sarcoidosis twice at least 1 month apart and any tissue biopsy result with the word “granuloma” defined in the biopsy report were considered to have sarcoidosis. Data regarding patients were obtained by using Turkish Ministry of Health National Electronic Data base. Patients of the formed cohort were investigated for the presence of a cranial imaging at any time. Results: 4367 patients were defined as sarcoidosis and enrolled in the study. 1659 cranial imagings in 689 patients were investigated. 1175 imagings were deemed suitable and evaluated. 3.4% of the patients had findings suggestive of sarcoidosis. Most common lesions were leptomeningeal or dural thickening with/without contrast material enhancement and midbrain/brainstem lesions. Presence of pulmonary sarcoidosis was the only significant factor with a negative predictive effect for patients to have typical findings.Discussion: Among sarcoidosis patients with MRI we detected 3.4% of them had findings suggestive of CNS sarcoidosis. Absence of pulmonary involvement was observed to be predictor for occurrence of typical manifestations.